Treatment efficacy and safety of drug-eluting beads transarterial chemoembolization versus conventional transarterial chemoembolization in hepatocellular carcinoma patients with arterioportal fistula. Issue 1 (31st December 2022) - Cai, Liang; Li, Honglu; Guo, Jiang; Zhao, Wenpeng; Duan, Youjia; Hou, Xiaopu; Cheng, Long; Du, Hongliu; Shao, Xihong; Diao, Zhenying; Hao, Yiwei; Zheng, Xinmei; et al.
ABSTRACT: This study aimed to compare the treatment efficacy and tolerance between drug-eluting beads transarterial chemoembolization (DEB-TACE) and conventional transarterial chemoembolization (cTACE) in hepatocellular carcinoma (HCC) patients with arterioportal fistula (APF). A total of 44 HCC patients with APF scheduled for DEB-TACE (N = 24, as DEB-TACE group) or cTACE (N = 20, as cTACE group) were recruited. Treatment response, hepatic function, and adverse events were assessed or recorded. Besides, progression-free survival (PFS) and overall survival (OS) were calculated. Total treatment response was better in the DEB-TACE group compared with the cTACE group ( P = .012). Meanwhile, the objective response rate (87.5% versus 60.0%) was higher ( P = .013), while the disease control rate (95.8% versus 85.0%) was similar in the DEB-TACE group compared to the cTACE group ( P = .213). Besides, PFS (mean value: 12.2 (95%CI: 9.9–14.6) months versus 7.8 (95%CI: 5.6–10.0) months) ( P = .037), but not OS (mean value: 20.0 (95%CI: 18.1–21.9) months versus. 18.6 (95%CI: 15.4–21.8) months) ( P = .341) was prolonged in DEB-TACE group compared with cTACE group. Regarding the safety, Child-Pugh stage, albumin level, and bilirubin level after treatment were all similar between the DEB-TACE group and cTACE group (all P > .05); moreover, no difference was found in the occurrence of adverse events during or after treatment between the two groups (all P > .05). Moreover, subsequent analyses found that embolic materials for APF (microspheres) in the DEB-TACE group did not affect the treatment efficacy (all P > .05). DEB-TACE promotes treatment response and PFS compared with cTACE and shows good safety in HCC patients with APF.